Assessment of Open Defecation Free (ODF) Campaign of Birgunj Sub Metropolitan City By Fecal Indicator Microbes Analysis - Shrivastava, Umesh Prasad (Academic Voices: A Multidisciplinary Journal, 2018)
Eliminating open defecation is increasingly seen as a key health outcome, improved educational and positive health outcomes for people. Several countries including Nepal have set aggressive targets for elimination of Open Defecation in urban and rural areas, which often include not only safe disposal of feces, but handwashing facilities, cleanliness and solid waste management. This paper is prepared based on the evaluation of representative water reservoirs of six sites of Birgunj municipality with an objective to examine fecal microorganisms. Presence of Cryptosporidium, Giardia, Citrobacter, Enterobacter, Klebsiella, Escherichia etc were observed. Although these wards have been declared ODF by municipality. This paper report the partial success toward ODF in Birgunj metropolitan and recommend post monitoring for ODF for sustainable ODF is required. Academic Voices Vol.6 2016: 55-62